The role of sphingolipid rheostat in the adult-type diffuse glioma pathogenesis - Karmelić, Ivana; Jurilj Sajko, Mia; Sajko, Tomislav; Rotim, Krešimir; Fabris, Dragana (Frontiers in Cell and Developmental Biology, 2024)
Gliomas are highly aggressive primary brain tumors, with glioblastoma multiforme being the most severe and the most common one. Aberrations in sphingolipid metabolism are a hallmark of glioma cells. The sphingolipid rheostat represents the balance between the pro-apoptotic ceramide and pro-survival sphingosine-1-phosphate (S1P), and in gliomas it is shifted toward cell survival and proliferation, promoting gliomas’ aggressiveness, cellular migration, metastasis, and invasiveness. The sphingolipid rheostat can be altered by targeting enzymes that directly or indirectly affect the ratio of ceramide to S1P, leading to increased ceramide or decreased S1P levels. Targeting the sphingolipid rheostat offers a potential therapeutic pathway for glioma treatment which can be considered through reducing S1P levels or modulating S1P receptors to reduce cell proliferation, as well as through increasing ceramide levels to induce apoptosis in glioma cells. Although the practical translation into clinical therapy is still missing, sphingolipid rheostat targeting in gliomas has been of great research interest in recent years with several interesting achievements in the glioma therapy approach, offering hope for patients suffering from these vicious malignancies.